Agricultural work and the risk of Parkinson's disease in Denmark, 1981-1993 - Tüchsen, Finn; Astrup Jensen, A. (Scandinavian Journal of Work, Environment & Health, 2000)
' ' OBJECTIVES ': 'This study examined the possible association between agricultural and horticultural work and the subsequent morbidity of Parkinson's disease.' ' METHODS ': 'Fixed cohorts of 2 273 872 men and women aged 20-59 years on 1 January 1981 and identified in the Central Population Register of Denmark were followed, and all first-time hospitalizations with Parkinson's disease as the principal diagnosis during the 13 years until 31 December 1993 were recorded. Standardized hospitalization ratios (SHR) were calculated using all gainfully employed persons as the standard and by multiplying the ratio by 100. Ninety-five percent confidence intervals (95% CI) were calculated on the assumption of a Poisson distribution.' ' RESULTS ': 'A high risk of Parkinson's disease was found for the men and women in agriculture and horticulture (134 cases, SHR 132, 95% CI 111-156). Statistically significantly high risks were found for farmers (79 cases, SHR 130, 95% CI 103-163) and for all men in agriculture and horticulture (109 cases, SHR 134, 95% CI 109-162).' ' CONCLUSIONS ': 'A consistent pattern of high Parkinson's disease morbidity was found among occupational groups employed in agriculture and horticulture.
Keywords: agricultural work; agriculture; Denmark; epidemiology; farming; horticulture; human; Parkinson’s disease; pesticide; risk; rural living